Demonstrating service delivery models for effective initiation and retention on pre-exposure prophylaxis (PrEP) among female bar workers in Dar es Salaam, Tanzania: a double randomized intervention study protocol - Chebet, Joy J.; Akyoo, Winfrida Onesmo; Goymann, Hannah; Harling, Guy; Barnhart, Dale A.; Mosha, Idda H.; Kamori, Doreen Donald; Gandhi, Monica; Mbunda, Theodora; Kipeleka, Judith; Sando, David; Spiegelman, Donna; et al. (PLOS ONE, 2024)
Background Pre-Exposure Prophylaxis (PrEP) has demonstrated efficacy in preventing HIV infection. Female Bar Workers (FBWs) often act as informal sex workers, placing them at risk of HIV infection. Despite expressing interest in PrEP, FBWs face barriers to accessing public-sector clinics where PrEP is delivered. We developed a study to compare the effectiveness of workplace-based PrEP provision to standard-of-care facility-based provision for PrEP initiation, retention and adherence among FBWs. Methods In this double-randomized intervention study, FBWs aged 15 years and above will be screened, consented and initiated on PrEP (emtricitabine/tenofovir disoproxil), and followed for six months. Participants will be randomized at the bar level and offered PrEP at their workplace or at a health facility. Those who are initiated will be independently individually randomized to either receive or not receive an omni-channel PrEP champion intervention (support from an experienced PrEP user) to improve PrEP adherence. We expect to screen 1,205 FBWs to enroll at least 160 HIV negative women in the study. Follow-up visits will be scheduled monthly. HIV testing will be performed at baseline, month 1, 4 and 6; and TDF testing at months 2 and 6. Primary outcomes for this trial are: (1) initiation on PrEP (proportion of those offered PrEP directly observed to initiate PrEP); and (2) adherence to PrEP (detectable urine TDF drug level at 6-months post-enrollment). The primary outcomes will be analyzed using Intention-to-Treat (ITT) analyses. Discussion Using a randomized trial design, we will evaluate two interventions aiming to reduce barriers to uptake and retention on PrEP among FBWs, a vulnerable population at risk of HIV acquisition and onward transmission. If these interventions prove effective in promoting PrEP among FBWs, they could assist in abating the HIV epidemic in Africa. Trial registration Registered with German Clinical Trials Register (www.drks.de) on 29 April 2020; Registration number DRKS00018101.
Gesehen am 25.02.2025